Climate Change as a Determinant of Mental and Physical Health: A Review - Abhinav Sahay; Upanshu Mishra; Arundhati Sharma; Badshah Alam; Rashmi Shekhar; Arvind Kumar Mishra (Journal of Psychosexual Health, 2026)
Objective: Environmental pollution is now a leading public health crisis around the world and fulfills the criteria of an environmental risk factor that impacts more than the well-recognized cardiopulmonary diseases; it is now recognized to affect mental, neurodevelopmental, reproductive, and pregnancy health as well. The goal of this review was to consolidate existing evidence on the effects of environmental pollutants, including air pollutants, endocrine-disrupting chemicals, heavy metals, persistent organic pollutants, pesticides, per- and polyfluoroalkyl substances (PFAS) and emerging pollutants such as microplastics, and the shared biological processes that connect these exposures to harmful health effects. Methods: A narrative review of all peer-reviewed publications from 2000 to 2025 was performed by searching through PubMed/MEDLINE, Scopus and Web of Science. Studies examining associations of environmental pollutants and mental health, neurodevelopmental, reproductive, and pregnancy outcomes were reviewed with a focus on systematic reviews, meta-analyses, cohort studies, biomonitoring investigations, and mechanistic studies. Cumulative and lifelong environmental exposures were assessed by evidence synthesis based on the exposome framework. Results: The studied evidence shows consistent relationships between PM, NO 2 , bisphenols, phthalates, PFAS, pesticides, heavy metals (specifically lead, mercury, and cadmium), polychlorinated biphenyls, dioxins and microplastics and elevated risk of depression, anxiety, cognitive impairment, impaired neurodevelopment, decreased semen quality, diminished fecundability, ovarian dysfunction, altered pubertal development, adverse pregnancy outcomes, placental injury, and fetal growth abnormalities. These harmful effects are achieved via common biological pathways such as oxidative stress, neuroinflammation, endocrine disruption, mitochondrial dysfunction, immune dysregulation, vascular injury, and epigenetic changes. There is also evidence that combined exposure to several pollutants can have additive or synergistic effects, and that sensitive groups to pollution exposure include pregnant women, children, and socio-economically disadvantaged groups. Conclusion: Pollution has emerged as an important and increasing concern from a life course perspective on mental and reproductive health. The exposome concept provides a simplified framework to understand cumulative environmental exposures and their health effects. Enforcing polluter accountability, curbing the use of hazardous substances, better monitoring exposure to pollution, better monitoring of reproductive and mental health outcomes, and incorporating pollution into public health policies are critical steps to curbing the disease burden of pollution and to safeguarding sensitive populations.